Aerodynamics Optimization of the Univeniti Teknologi PETRONAS 'PERODUA Eco-ChaUenge 2011' Car - ROSLAN, MUHAMMAD SHAFIQ (Universiti Teknologi Petronas, 2011)
This is the construction and report on the experimentation of a shape-optimization method applied to aerodynamic design of a car. The scopes of study areas are in research, designing and analysis in computational fluid dynamics tool. The significance of this research would be important to evaluate the condition of the final model that posses the best drag coefficient This research starts by searching for any other relevant journal or article published by other researches and from there, the design would be review and useful information will be summarize and taken as an information to this research. From the data available from the model, the drag coefficient will be calculated manually and also by using software. CATIA v5, GAMBIT v2.2.30 and FLUENT v6.3.26 software are then used to design analyze the air flow behavior. The result from the computational fluid dynamics software will be compare with the result from wind tunnel experiment.